COMPARISON OF INDONESIAN TUNA LONGLINE FISHING PERFORMANCE WITHIN AND OUTSIDE INDONESIA EXCLUSIVE ECONOMIC ZONE (EEZ) - Bram Setyadji; Irwan Jatmiko (Research Center for Fisheries, 2017)
Indonesian tuna longline fleets have been fishing in the Exclusive Economic Zone (EEZ) and high seas of the Indian Ocean for quite some time. However, effort has never been made to separate catch from the EEZ and the high seas as it important for fisheries management. A total of 2,430 set-by-set longline fishing data had been collected by scientific observers based in the Research Institute of Tuna Fishery in Bali since August 2005 to December 2014 on which present analysis was made. The research aims to compare between trend of tuna catch of the EEZ and of the high seas of Indian Ocean. The results show that the mean hook rate of both catches of big eye tuna (BET) and southern Bluefin tuna (SBT) caught in the high seas was significantly higher than that the EEZ (two sample t-test, p<0.05), while for yellow fin tuna (YFT) it was in the opposite direction (two sample t-test, p<0.05). As for albacore (ALB), the mean hook rate value was statistically similar in both fishing grounds (two sample t-test, p>0.05).